Factors affecting supervisors' enactment of interpersonal fairness: The interactive relationship between their managers' informational fairness and supervisors' sense of power. (14th July 2020) - Brockner, Joel; De Cremer, David; van Dijke, Marius; De Schutter, Leander; Holtz, Brian; Van Hiel, Alain
Summary: Managerial trickle‐down effects refer to the tendency for supervisors to treat their subordinates in ways analogous to how they have been treated by their own bosses. Although trickle‐down effects are widely documented, including in the justice literature, less is known about the conditions under which they are more versus less likely to emerge. Across two studies, we examined how supervisors' tendencies to exhibit interpersonal fairness are interactively determined by the informational fairness they receive from managers above them and supervisors' sense of power. Study 1 was a multisource survey conducted in organizational settings. Study 2 was an experiment in which we manipulated the informational fairness that supervisors received from managers and supervisors' sense of power. The results of both studies showed that the positive relationship between the informational fairness received from managers and supervisors' enactment of interpersonal fairness was stronger among supervisors who had a lower sense of power. This interactive effect did not emerge on supervisors' enactment of other forms of fairness (distributive, procedural, and informational), consistent with prior theory and research showing that interpersonal fairness allows for greater discretion than other forms of fairness. Theoretical and practical implications are discussed as are limitations and suggestions for future research.